2020
DOI: 10.1093/cid/ciaa1824
|View full text |Cite
|
Sign up to set email alerts
|

The Spectrum of Tuberculosis Disease in an Urban Ugandan Community and Its Health Facilities

Abstract: Background New, sensitive diagnostic tests facilitate identification and investigation of milder forms of tuberculosis (TB) disease. We used community-based TB testing with the Xpert MTB/RIF Ultra assay (“Ultra”) to characterize individuals with previously undiagnosed TB and compare them to those from the same community who were diagnosed with TB through routine care. Methods We offered community-based sputum Ultra testing to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 11 publications
(20 reference statements)
6
10
0
Order By: Relevance
“…National TB prevalence survey estimates are based on 2 specimens and our estimate is therefore likely to underestimate prevalence compared with the national survey and other surveys in which multiple samples are collected. Our community estimates are consistent with those reported in a recent study from Uganda based on a single sputum specimen tested with Xpert Ultra [24]. Including all Xpert Ultra-positive tests resulted in an estimated community prevalence of 940 (95% CI, 780-1130) per 100 000 and 420 (95% CI, 320-550) per 100 000 adults when Xpert Ultra trace-positive and culture-negative sputum results were excluded.…”
Section: Muacsupporting
confidence: 87%
See 1 more Smart Citation
“…National TB prevalence survey estimates are based on 2 specimens and our estimate is therefore likely to underestimate prevalence compared with the national survey and other surveys in which multiple samples are collected. Our community estimates are consistent with those reported in a recent study from Uganda based on a single sputum specimen tested with Xpert Ultra [24]. Including all Xpert Ultra-positive tests resulted in an estimated community prevalence of 940 (95% CI, 780-1130) per 100 000 and 420 (95% CI, 320-550) per 100 000 adults when Xpert Ultra trace-positive and culture-negative sputum results were excluded.…”
Section: Muacsupporting
confidence: 87%
“…In both surveys, most participants with culture-positive sputum did not report any symptoms, although reporting TB symptoms was associated with having culture-positive sputum. This has been reported in other community-based TB prevalence surveys [22][23][24] but not previously reported among adult clinic attendees. The degree of infectiousness of asymptomatic individuals with subclinical disease compared with symptomatic people is not known [25,26].…”
Section: Discussionsupporting
confidence: 63%
“…This finding is in line with a recent study from a population-based screening in urban Uganda, which showed that individuals newly diagnosed with active TB in community-based screening have fewer symptoms, compared to people diagnosed at health facilities. 29 It is also in line with the recently completed South African National TB prevalence survey (57.7% asymptomatic) 30 and a recent meta-analysis of global TB prevalence surveys (79-97% asymptomatic) 31 . Asymptomatic TB eludes traditional symptom-based TB screening algorithms but is identifiable by CXR abnormality in most cases.…”
Section: Discussionsupporting
confidence: 81%
“…This analysis was conducted as part of the STOMP-TB (Strategies for Treating, Observing, Managing, and Preventing Tuberculosis) study, an ongoing population-based study in a densely populated area consisting of 37 contiguous administrative zones in Kampala, Uganda (estimated population: 50,436, total area 2.2 km 2 [ 28 ]). The STOMP-TB study enrolls patients through two mechanisms: health facility TB diagnostic testing (from May 2018-July 2021) and active community outreach and testing (Phase 1 conducted from February to December 2019).…”
Section: Methodsmentioning
confidence: 99%